Rac1 is Required for Matrix Metalloproteinase-13 Production by Chondrocytes in Response to Fibronectin Fragments - Long, David L. (2013)
OBJECTIVE: Matrix fragments, including fibronectin fragments (Fnf), accumulate during the development of osteoarthritis (OA) stimulating chondrocyte matrix metalloproteinase (MMP) production. The objective of this study was to determine the role of the small GTPase Rac1 in chondrocyte signaling stimulated by Fnf that results in MMP-13 production. METHODS: Normal human cartilage was from tissue donors and OA cartilage from knee arthroplasty specimens. Rac1 activity was modulated with a chemical inhibitor, siRNA knock-down, constitutively active (CA)-Rac or dominant negative (DN)-Rac adenovirus. Cells were treated with Fnf or without known Rac activators, epidermal growth factor (EGF) or transforming growth factorα (TGFα). Rac1 activity was measured with a colorometric activity ELISA, pulldown assay, and immunostaining with a monoclonal antibody against active Rac. RESULTS: Chemical inhibition of Rac1, as well as knockdown by siRNA and expression of DN-Rac blocked Fnf stimulated MMP-13 production while expression of CA-Rac increased MMP-13. Inhibition of Rho-associated kinase had no effect. EGF and TGFα, but not Fnf, increased Rac1 activity and promoted the increase in MMP-13 above that stimulated by Fnf alone. Active Rac was detected by immunostaining in OA cartilage. CONCLUSION: Rac1 is required for Fnf induced signaling that results in increased MMP-13 production. EGF receptor ligands, which activate Rac, can promote this effect. The presence of active Rac in OA cartilage and the ability of Rac to stimulate MMP-13 production suggests that it could play a role in the cartilage matrix destruction seen in OA.